Impact of Inflation on University Administration in Nigeria - Ogunode, Niyi Jacob; UKOZOR, Conrad Ugochukwu (Research Parks Publishers, 2023)
Inflation is the continuous rise in the general price of goods and services. Inflation is an economic problem that affects institutional operation both public and private institutions. This paper examined the impact of inflation on university administration in Nigeria. Depending on secondary data were collected from both print and online publications. The paper established that inflation has led to an increment in the operational cost of running universities, an increment in the cost of infrastructure facilities provision, an increment in the cost of teaching program implementation, an increment in the cost of research programme implementation and an increment in cost of community programme implementation, increment in universities fees and increment in students drop out. Based on the impacts of inflation on university administration in Nigeria, the paper hereby recommended the following: The government should increase the funding of universities. Universities administrators increase the internally generated revenue by embarking on different ventures to raise more revenue. The government should put policies down to encourage production and reduce importation.